SARGoT:Smart Autonomous Robotic Goods Transporter. (2020) - Abraham, Akhil; Ananthakrishnan, G.S.; Varghese, Bijeesh B.; Sivakumar, S.; Rakesh, S.
Abstract: In the present condition industrial loading and unloading of heavy loads manually is one of the most important objectives which turn out to be quite difficult, time-consuming and risky for humans. In this modern era robots are being developed for various purposes to accomplish many tasks which seem to be too complex for humans. The advantage of using robots, for industrial purpose have been excellent in terms of speed and efficiency of doing required tasks compared to that of humans. To solve this problem we have designed a robot named SARGoT. This robot has got mainly three features and they are: Path-Tracking. Avoiding Collision, Loading and Unloading heavy industrial goods. The autonomous robot is designed to start its movement from a starting position where goods are loaded on it, then follow a black track and unload goods by itself after reaching a destination place. Infrared sensor has been mounted in the front of the robot so that the sensor can detect path by emitting and receiving signals allowing it to move in the predefined path having left and right turns to carry goods from starting position to the destination position. Arduino Uno has been used for the coding section and the control circuit of the robot has been implemented for controlling the robot's movement within the defined track. The robot has been designed in such a way that it has the ability to avoid collision with any obstacles that come in its way. Ultrasonic sensor has been used in the robot to send the signal and detect the presence of any obstacle that may appear in the robot's track and stop momentarily for certain time until the obstacle move away. Building an industrial robot with moderate Speed, good efficiency in loading and unloading purpose within a short time to ease human suffering has been the main objective of this paper.